Nursing Student's Perceptions of the Clinical Learning Environment, Supervision and Nurse Teacher: A Cross-Sectional Study - Anita Karaca; Gizem Kaya; Nezihe Kizilkaya Beji (Atatürk University, 2024)
Objective: This study aimed to determine nursing students' perceptions of the clinical learning environment, supervision and nurse teacher, and its affecting factors. Methods: This cross-sectional and descriptive study was conducted with 205 students using the Student Information Form and the Clinical Learning Environment, Supervision and Nurse Teacher Evaluation Scale. The study included 1st, 2nd, 3rd and 4th year nursing students studying in the spring semester of 2020-2021. Data were collected by online method. Descriptive statistics (means, frequencies and percentages), Mann-Whitney U and Kruskal-Wallis analyses were used to analyze the data.Results: The students of 59.5% stated their opinions were not taken during clinical practice placement, whereas 71.2% of them were placed in the compatible clinical environment. The students did not experience any problems during their clinical practice (77.6%) and they evaluated their satisfaction as "good" (37.6%). The lowest and highest sub-dimension scores from the scale were the "Pedagogical Atmosphere on the Ward (3.71±1.15)" and the "Premises of Nursing on the Ward (3.93±1.13)", respectively. The sub-dimension mean scores of the scale were significantly different from satisfaction with clinical practice, problems encountered during clinical practice, and placement in the compatible clinical environment (P<.001). Conclusion: Nursing students had a good perception of the supervision, learning environment, and nurse teacher. A positive clinical environment for nursing students that allows them to take an active role in patient care and nursing practice should be developed and maintained.